Low rate of life‐threatening events and limitations in predicting invasive and noninvasive markers of symptoms in a cohort of type 1 Brugada syndrome patients: Data and insights from the GenBra registry. (5th October 2020) - Sacilotto, Luciana; Scanavacca, Mauricio I.; Olivetti, Natália; Lemes, Carolina; Pessente, Gabrielle D.; Wulkan, Fanny; Hachul, Denise T.; Krieger, Jose E.; Pereira, Alexandre C.; Darrieux, Francisco C. C.
Abstract: Background: Brugada syndrome (BrS) has diagnostic challenges and controversial risk assessment. We aimed to investigate invasive and noninvasive parameters in symptomatic and asymptomatic patients from a Brazilian cohort of type‐1 BrS. Methods: Patients with spontaneous and drug‐induced type‐1 BrS were classified into two groups, asymptomatic ( n = 116, 84.1%) and symptomatic ( n = 22, 15.9%; 13 with arrhythmogenic syncope, 9 with aborted sudden cardiac death). Genetic testing, EPS parameters, and electrocardiogram (ECG) parameters were analyzed. Results: A total of 138 consecutive patients were eligible, 101 men (73.2%), mean 41.4 years, mostly probands (79%). Spontaneous pattern, observed in 77.5% of the patients, was associated with symptoms only if expressed in V1 and V2 standard position (not high precordial leads; p = .014). All symptomatic patients were probands. The presence of right ventricular outflow tract conduction delay (RVOTcd) signs, positive EPS, and SCN5A status was similar between symptomatic and asymptomatic subjects. During the mean 75‐month follow‐up, eight patients had appropriate therapies. All had spontaneous type‐1 ECG pattern and 2/8 (25%) were asymptomatic, with positive EPS. The overall LAE incidence of 1.1% per year dropped to 0.27% in asymptomatic patients. RVOTcd occurred more frequently in SCN5A carriers (QRS‐f 33.3% vs. 7.7%; p = .005, AVR sign 58.3% vs. 13.6%; p < .001; deep S in lead I 75% vs. 48.5%, p = .025%), as well as longer HV interval (66 vs. 49 ms; p < .001). Conclusions: Spontaneous type‐1 Brugada pattern in standard leads and proband status were more frequent in symptomatic subjects. RVOTcd, more common in SCN5A carriers, did not predict symptoms in BrS patients. EPS exhibited limited prognostic value for this low‐risk population.